Complex Adaptive Systems Modeling: A multidisciplinary Roadmap - Niazi, Muaz A (Complex adaptive systems modeling, 2013)
PAC Codes 07.05.Tp, 89.75.-k, 89.75.Fb Mathematics Subject Classification (2010) 05C82, 68T42, 00A72, 92C42